Colombian university publishers - Restrepo-Arango, Cristina (2023)
Objective: Characterize the Colombian university presses. Method: Use Microsoft Excel to manipulate the information. Result: 103 IES (27%) were found that have a university press (EU), of which 63 EIS (61%) are accredited of high quality, 20 are public and 43 are private. Only 68 publishers publish scholarly books in print, while 87 EU publishers publish digital books. University publishers publish electronic books located mostly in Bogotá (36 publishers, 41%), Antioquia (18 publishers, 20%), Valle del Cauca (seven publishers, 8%) and Atlántico (four publishers, 5%). Open access is provided by 67 academic publishers (65%), of which 29 academic publishers are concentrated in Bogotá (42%), 12 in Antioquia (17%), seven in Cali (10%), and three in Atlántico (4%). Online purchase is facilitated by 48 publishers, purchasing books in print or electronic format directly from the academic publisher. There are 70 publishers that are part of ASEUC (68%) and they are located in 19 departments specifically in 16 capital cities, while three are located in Mosquera (Cundinamarca) and Envigado (Antioquia). Conclusions: it characterizes the Colombian university publishing houses and identified that the EU are concentrated in the main capital cities such as Bogotá, Cali and Medellín, because these cities are where most of the HEIs in the country are.